Pathological-Condition-Driven Construction of Supramolecular Nanoassemblies for Bacterial Infection Detection - Li, Li-Li; Ma, Huai-Lei; Qi, Guo-Bin; Zhang, Di; Yu, Faquan; Hu, Zhiyuan; Wang, Hao (Advanced materials (Weinheim), 2016)
A pyropheophorbide‐α‐based building block (Ppa‐PLGVRG‐Van) can be used to construct self‐aggregated superstructures in vivo for highly specific and sensitive diagnosis of bacterial infection by noninvasive photoacoustic tomography. This in vivo supramolecular chemistry approach opens a new avenue for efficient, rapid, and early‐stage disease diagnosis with high sensitivity and specificity.